Hubungan antara Tingkat Konsumsi Protein dan Lama Hemodialisis dengan Status Gizi Pasien Gagal Ginjal Kronis di RSUD Wangaya Denpasar - Anak Agung Istri Kencana Sari Devi; Ni Komang Wiardani; Lely Cintari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Chronic kidney failure is a clinical condition characterized by progressive decline in kidney function. The purpose of this study was to determine the relationship between the level of protein consumption and length of hemodialysis with the nutritional status. This type of observational research with cross sectional design. A sample of 34 people was determined by consecutive sampling. Data collected in the form of sample characteristics, level of protein consumption, length of hemodialysis, and nutritional status were obtained through interview, anamnesa and physical examination, as well as recording medical record data. Based on the criteria for the level of protein consumption the results obtained were 31 people (91.2%) who were not in accordance with their daily protein needs. Most of the samples undergoing hemodialysis were 3 years, as many as 15 people (44.1%). The most nutritional status of the sample is in the category of mild to moderate malnutrition with an indicator of nutritional status in the range of scores from 14-23 as many as 19 people (55.9%). Spearman Rank correlation test results found no relationship (p value = 0.70) between the level of protein consumption with the nutritional status, with (r value = -0.06) and no relationship (p value = 0.08) between length of hemodialysis with the nutritional status (r = 0.29). The conclusion of this study is that there is no relationship between the level of protein consumption and length of hemodialysis with the nutritional status of patients with chronic kidney failure at Wangaya Regional General Hospital Denpasar. Keywords: Chronic Kidney Failure, Level of Protein Consumption, Length of Hemodialysis, Nutritional Status